Masdevallia leonor-baeziana (Pleurothallidinae) : a new species from the Andean-Amazonian foothills of Caquetá, Colombia - Perdomo, Oscar; Trujillo Trujillo, Edwin; Karremans Lok, Adam Philip (2023)
We describe and illustrate a new species of Masdevallia from the Andean-Amazonian foothills of Caquetá, Colombia. Masdevallia leonor-baeziana belongs to Masdevallia subsect. Saltatrices,within the M. constricta group. It is most similar to M. constricta, but it can be distinguished by the shorter sepals and sepaline tails that do not surpass the tube length, and the shorter, sigmoid-ovate lip. We proposed categorizing the species as Critically Endangered (CR) based on the B and D IUCN red list criteria.
Describimos e ilustramos una nueva especie de Masdevallia del piedemonte Andino-Amazónico de Caquetá, Colombia. Masdevallia leonor-baeziana pertenece a Masdevallia subsecc. Saltatrices, dentro del grupo M. constricta. Es similar a M. constricta, pero puede diferenciarse por los sépalos y colas sepalinas más cortos que no sobrepasan el largo del tubo, y el labelo más corto, sigmoide-ovado. Proponemos la categorización de la especie como Críticamente Amenazada (CR) siguiendo los criterios B y D de la lista roja de la IUCN.
Keywords: MASDEVALLIA -- IDENTIFICACIÓN -- CAQUETA (COLOMBIA); ESPECIES -- IDENTIFICACION; ORQUIDEAS -- CAQUETA (COLOMBIA)